Foreign body aspiration in children: The value of diagnostic criteria - KIYAN, GÜRSU (ELSEVIER IRELAND LTD, 2009)
Objective: Foreign body aspiration (FBA) is a serious problem in children. While bronchoscopy should be performed in all patients with aspiration; patients without aspiration should be carefully excluded to avoid an unnecessary bronchoscopy. In this study we analyzed the details of our series, complication rates and compared the diagnostic findings between patients with an aspirated FB and those without. We also calculated the sensitivities, specificities, positive predictive values and negative predictive values of clinical history, symptoms, physical examination findings and radiological findings in patients with suspected FBA (sFBA). Finally, we evaluated the validity of our bronchoscopy indications in these patients. Methods: We reviewed the data of 207 patients who underwent rigid bronchoscopy for sFBA. We used clinical history, symptoms, physical examination and radiological findings as diagnostic findings. Complication rates in addition to these four diagnostic criteria constitute our indications for performing a rigid bronchoscopy. Results: After excluding 15 patients with radiopaque FB or previous fiberoptic bronchoscopy, 138 of 192 patients had an aspirated foreign body. The sensitivity and specificity of clinical history, symptoms, physical examination findings and radiological findings were 90.5% and 24.1%, 97.8% and 7.4%, 96.4% and 46.3, and 71.7% and 74.1% respectively. There was only one major complication which caused moderate neurological sequelae. There was no mortality and no thoracotomy or tracheotomy requirement in this group. Conclusions: While symptoms, physical examination findings and clinical history had high sensitivities, radiological findings had the highest specificity. Low specificities of clinical history, symptoms and physical examination findings were due to our expanded bronchoscopy indication, which aimed to include all patients with foreign body aspiration. Our low complication rate facilitated the expansion of bronchoscopy indications, even for patients with slight clinical suspicion. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Foreign body aspiration; Airway; Children; Bronchoscopy; PLAIN CHEST RADIOGRAPHY; BRONCHOSCOPIC REMOVAL; DELAYED PRESENTATION; BODIES; MANAGEMENT; EXPERIENCE; HISTORY; AIRWAY; COMPLICATIONS